The Burden and Benefits of Knowledge: Ethical Considerations Surrounding Population-Based Newborn Genome Screening for Hearing - Calli O. Mitchell; Greysha Rivera-Cruz; Matthew Hoi Kin Chau; Zirui Dong; Kwong Wai Choy; Jun Shen; Sami Amr; Anne B. S. Giersch; Cynthia C. Morton (International Journal of Neonatal Screening, 2022)
Recent advances in genomic sequencing technologies have expanded practitioners’ utilization of genetic information in a timely and efficient manner for an accurate diagnosis. With an ever-increasing resource of genomic data from progress in the interpretation of genome sequences, clinicians face decisions about how and when genomic information should be presented to families, and at what potential expense. Presently, there is limited knowledge or experience in establishing the value of implementing genome sequencing into newborn screening. Herein we provide insight into the complexities and the burden and benefits of knowledge resulting from genome sequencing of newborns.